A survey of empirical studies using transaction level data on exports and imports - Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2015)
This paper presents a tabular survey of 146 empirical studies for 39 countries, plus 8 studies for multiple countries, that use transaction level data on exports or imports of firms. I hope this survey is useful for readers who want to get an impression of the huge number of different topics that have been investigated with transaction level data for a large number of countries already; who want to learn whether transaction level data have already been used for a particular (maybe, their own) country, by whom they have been used to investigate which topics, and what the important results found are; who have access to transaction level data and an idea how to use them, and who want to find out whether others pursued the same or a similar topic already; who want to compare results from their own study based on transaction level data to results from other (similar, neighbor) countries and who are looking for suitable studies; who have access to transaction level data and who are looking for studies based on data from other countries that they can replicate with their data to uncover and investigate differences across countries, or to contribute to the unravelling of stylized facts that hold across countries (and time).
Keywords: 330